Álvaro Siza, escultor - Silva, Ana Filipa Simões da (2017)
About the architect who wanted to be a sculptor, this article intends to explore Álvaro Siza's approach to sculpture. Being his artistic production developed under the existence of this original vocation associated with an architectural formation and practice, Siza's work naturally presents itself as an outcome of the relation between the two arts